2019
DOI: 10.1055/s-0039-1696956
|View full text |Cite
|
Sign up to set email alerts
|

High Medium-Term Survivorship of Cruciate-Retaining Total Knee Arthroplasties (110 Knees) for Valgus Deformity

Abstract: The main purpose of this article is to evaluate the clinical outcomes and survivorship of cruciate-retaining (CR) knee arthroplasties for valgus deformity. This article is retrospective consecutive series of 110 valgus knees using CR implants with a minimum 2-year follow-up. Deformity correction was achieved using stepwise sequential soft tissue releases (iliotibial band, popliteus tendon, lateral collateral release through sliver femoral condylar osteotomy). Demographic data, range of movement, and degrees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The obtained overall CPNP ratio of 1.9% in this study falls within the known range of TKA-V (0.3% -9.5%) [3,[9][10][11][12][13][14][15][16][17]. Other systematic review reported a range of 0.01% to 4.3%, like the one of Carender et al [2] and Rodríguez-Merchán et al [50].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The obtained overall CPNP ratio of 1.9% in this study falls within the known range of TKA-V (0.3% -9.5%) [3,[9][10][11][12][13][14][15][16][17]. Other systematic review reported a range of 0.01% to 4.3%, like the one of Carender et al [2] and Rodríguez-Merchán et al [50].…”
Section: Discussionsupporting
confidence: 84%
“…An increased anatomical femorotibial angle (aFTA) of > 10° is commonly used to define a valgus knee [6][7][8]. In the literature, the reported CPNP incidence after TKA in valgus deformities with an aFTA > 10° (TKA-V) ranges between 0.3-9.5% [3,[9][10][11][12][13][14][15][16][17]. Injury of the common peroneal nerve (CPN) can be caused by indirect damage due to stretch or ischaemia after correction, or by direct injury due to laceration of the CPN during lateral soft tissue release (STR) [8,11,12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…At present, no consensus has been reached on the treatment of type II valgus deformity [12,13]. Compared with that on the medial side of the knee, the controllability of the release on the lateral side of the knee is imperfect, owing to the lack of soft tissue sleeve.…”
Section: Discussionmentioning
confidence: 99%